Professional Competency Management of Teachers in Improving the Quality of Meaningful Learning in Elementary Schools - Arif Rahman Hakim; Deti Rostini (Journal of Innovation and Research in Primary Education, 2026)
Improving meaningful learning quality in elementary schools requires systematic management of teacher professional competencies. This study examines how professional competency management contributes to meaningful learning implementation through Deming's Plan-Do-Check-Act (PDCA) cycle framework. A qualitative multiple case study was conducted at SDN Loji (Bandung Regency) and SDN Cikandang (Sumedang Regency), West Java, Indonesia. Data were collected through semi-structured interviews with principals and teachers, participatory observations, and document analysis. Data validity was established through triangulation, member checking, and peer debriefing. Analysis employed Miles and Huberman's interactive model. Both schools implemented all PDCA stages with varying sophistication levels. SDN Loji demonstrated structured approaches with comprehensive needs assessment, diverse training programs, systematic evaluation using multiple indicators, and responsive follow-up actions. SDN Cikandang, despite resource constraints, achieved meaningful development through collaborative peer learning, reflective practices, and adaptive strategies. Unexpected findings revealed that resource limitations fostered higher teacher agency and that informal learning networks generated stronger peer accountability than formal structures. The PDCA cycle effectively guides teacher competency management when adapted to institutional contexts. Success requires balancing systematic structures with professional autonomy, formal programs with informal collaboration, and organizational direction with teacher ownership. The study advances understanding of continuous improvement cycles in education and provides practical guidance for school leaders and policymakers.